The Effect of Wire Straighness Electric Current Variation on Size Diversion and Rude of The Cutting Current Profile of Medium Carbon Steel Dental from Wire (EDM) - Aladin Eko Purkuncoro; Anang Subardi; Achmad Taufik (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Wire Electric Discharge Machine (EDM) is a non-conventional metal cutting machine. This machine is commonly used to form machine components that have complex shapes and require high precision. Not many conventional and non-conventional machines are capable of producing small module gears. The cutting groove occurs from the erosion of the electric spark by the electrode wire moving from the coil of wire and forming or cutting the workpiece. One of the machining parameters that determine the quality of the product on an EDM wire is Current. So this study aims to determine the deviation of the gear profile cutting groove and the roughness that occurs in the straight gear profile cutting groove from the results of the Wire EDM process. In this thesis research, the varied parameters are electric current. The current used is 6 A, 7 A, 8 A, 9 A 10 A. The results of this research show that the current 6 A has an average deviation value of 0.0228 mm. At current 7 A has an average deviation value of 0.0255 mm. At current 8 A has an average deviation value of 0.0275 mm. At current 9 A has an average deviation value of 0.0313 mm. And at a current of 10 A has an average deviation value of 0.0362 mm. At current 6 A has an average roughness value. At current 7 A has an average roughness value. At current 8 A has an average roughness value. At current 9 A has an average roughness value. And at current 10 A has an average roughness value. This is due to the greater use of an electric current at the electric voltage, which will cause the sparking to get bigger too, this causes the movement of the electron flow to hit the surface of the workpiece faster, resulting in an increase in temperature which results in erosion of the workpiece surface. , this will change the result of the cut which affects the size precision and roughness of the wire EDM.